Oral bullous pemphigoid – a rarity among vesiculobullous lesions - P Venkatalakshmi Aparna (Journal of Indian Academy of Oral Medicine and Radiology, 2018)
Bullous pemphigoid (BP) otherwise known as parapemphigus is a chronic autoimmune subepidermal blistering disease with tense bullae that rupture and become flaccid. It commonly affects the skin and is rare in oral mucous membrane. Considering its rarity, we are presenting a case report of a 45-year-old female diagnosed with BP that had occurred predominantly in the oral cavity prior to the minimal presentation of skin lesions, along with satisfactory management, thereby stressing the role of dentists in prior diagnosing the lesion.